Targeting the N-Terminal Domain of the Androgen Receptor: A New Approach for the Treatment of Advanced Prostate Cancer. (14th September 2016) - Antonarakis, Emmanuel S.; Chandhasin, Chandtip; Osbourne, Erica; Luo, Jun; Sadar, Marianne D.; Perabo, Frank
Abstract : Despite the recent approval and widespread use of abiraterone acetate and enzalutamide for the treatment of castration-resistant prostate cancer (CRPC), this disease still poses significant management challenges because of various tumor escape mechanisms, including those that allow androgen receptor (AR) signaling to remain active. These AR-related resistance mechanisms include AR gene amplification or overexpression, constitutively active ligand-independent AR splice variants, and gain-of-function mutations involving the AR ligand-binding domain (LBD), among others. Therefore, the development of AR-targeted therapies that function independently of the LBD represents an unmet medical need and has the potential to overcome many of these resistance mechanisms. This article discusses N-terminal domain (NTD) inhibition as a novel concept in the field of AR-directed therapies for prostate cancer. AR NTD-targeting agents have the potential to overcome shortcomings of current hormonal therapies by inhibiting all forms of AR-mediated transcriptional activity, and as a result, may affect a broader AR population including mutational and splice variant ARs. Indeed, the first clinical trial of an AR NTD inhibitor is now underway. Abstract : This article discusses N-terminal domain (NTD) inhibition as a novel concept in the field of androgen receptor (AR)-directed therapies for prostate cancer. AR NTD-targeting agents have the potential to overcome shortcomings of current hormonal therapies by inhibiting all forms of AR-mediated transcriptional activity and, as a result, may affect a broader AR population, including mutational and splice variant ARs.